Analysis of the Impact of Indomaret's Presence on Retail Traders' Income in Poka Village, Teluk Ambon District - Louhenapessy, William George (JENDELA PENGETAHUAN, 2022)
This study aims to determine the income of retail traders before and after the presence of Indomaret in Poka Village, Teluk Ambon. This study uses a quantitative approach with statistical analysis paired sample t-test. The study population consisted of 310 retail traders in Poka Village who sold the same products as the products sold at Indomaret and a sample of 31 retail traders. The results of the study showed that there were changes in the income of retail traders before and after the presence of Indomaret in Poka Village, Teluk Ambon District, as seen from the raw data obtained by the researchers. Then, data analysis was carried out using statistical analysis, which included Homogeneity, Linearity, and Paired Sample T-test from the three tests showing that there were real or significant differences in the income of retail traders before and after the presence of Indomaret in Poka Village.